Application of Evolutionary Computation in Automotive Powertrain Mount Tuning - Anab Akanda; Chandu Adulla (Shock and Vibration)
Engine mount tuning is a multi-disciplinary exercise since it affects Idle-shake, Road-shake and power-train noise response. Engine inertia is often used as a tuned absorber for controlling suspension resonance related road-shake issues. Last but not least, vehicle ride and handling may also be affected by mount tuning. In this work, Torque-Roll-Axis (TRA) decoupling of the rigid powertrain was used as a starting point for mount tuning. Nodal point of flexible powertrain bending was used to define the envelop for transmission mount locations. The frequency corresponding to the decoupled roll mode of the rigid powertrain was then adjusted for idle-shake and road-shake response management.